2020
DOI: 10.1056/nejmoa1903297
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Oxygen Therapy during Mechanical Ventilation in the ICU

Abstract: Background: Patients who are going thorugh mechanical ventilation in the intensive care unit (ICU) often receive a high fraction of inspired oxygen (Fio2 ) and have a high arterial oxygen tension. The conservative use of oxygen may reduce oxygen exposure, diminish lung and systemic oxidative injury, and thereby increase the number of ventilator-free days (days alive and free from mechanical ventilation). Methods: We randomly assigned 1000 adult patients who were anticipated to require mechanical ventilation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
147
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(185 citation statements)
references
References 22 publications
5
147
3
4
Order By: Relevance
“…The results of the much larger ICU-ROX multi-centre study have been published very recently. 10 This study did not demonstrate any difference in the primary outcome measure (ventilator free days) or any significant difference in 180 day mortality between ventilated ICU patients randomised to conservative oxygen therapy (target saturation range 91-96%) compared with ''usual care'' (target range 591%). However, the mean PaO2 of these patients was not widely different (108mmHg / 14.4 kPa in the usual care group and 90 mmHg / 12.0 kPa in the conservative oxygen group).…”
Section: Introductioncontrasting
confidence: 53%
“…The results of the much larger ICU-ROX multi-centre study have been published very recently. 10 This study did not demonstrate any difference in the primary outcome measure (ventilator free days) or any significant difference in 180 day mortality between ventilated ICU patients randomised to conservative oxygen therapy (target saturation range 91-96%) compared with ''usual care'' (target range 591%). However, the mean PaO2 of these patients was not widely different (108mmHg / 14.4 kPa in the usual care group and 90 mmHg / 12.0 kPa in the conservative oxygen group).…”
Section: Introductioncontrasting
confidence: 53%
“…In randomized trials, "induced" hyperoxia (using 100% oxygen) increased 28-day mortality in septic shock patients [23], while critically ill patients randomized to a target arterial oxygen tension (PaO 2 ) of 70-100 mmHg had lower mortality compared to patients with a "conventional" target of PaO 2 up to 150 mmHg [24] in a single-center study. While a recent large international multicenter trial demonstrated no effect of conservative oxygen therapy in a diverse cohort of critically ill patients [25], a subsequent sub-study raised the possibility of clinically important harm with conservative oxygen therapy in patients with sepsis [26].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the findings of the intensive care unit randomized trial comparing two approaches to oxygen therapy (ICU-ROX) [9]. ICU-ROX compared conservative oxygen therapy with usual oxygen therapy in 1000 mechanically ventilated ICU patients.…”
Section: Introductionmentioning
confidence: 99%